Searching for Ariadne’s thread. Some remarks on urban resilience and orientation - Rabino, Giovanni; Cutini, Valerio (TeMA - Journal of Land Use, Mobility and Environment, 2012)
This paper concerns the methods of analysis of the configuration of the urban grids. More in details, it will focus on the configurational approach to the analysis of urban settlements, briefly presenting the different methods and techniques it has inspired, sketching their features, highlighting their actual utility and reminding their respective advantages and limits. Moreover, it will propose the use of some further configurational parameters, suitable for describing and reproducing interesting features of urban settlements; more in details, it will cast attention onto the richness and the variety of paths within a settlement, what makes it resilient, that is capable of sustaining changes and transformations without radically modifying its inner geography. Such parameters have been tested on the case studies of Pisa and Venice, which can easily be recognised as particularly relevant and significant, in that the results they provide are diametrically different. Those outputs will then be presented and discussed; the findings are suitable for suggesting resilience as a singular clue for urban orientation, so that the configurational techniques can be proposed as a tool for evaluating and predicting this spatial attitude, here finding an Ariadne’s thread for urban wayfinding.